Experience-Dependent Changes in Excitatory and Inhibitory Receptor Subunit Expression in Visual Cortex - Beston, Brett R.; Jones, David G.; Murphy, Kathryn M. (Frontiers in Synaptic Neuroscience, 2010)
Experience-dependent development of visual cortex depends on the balance between excitatory and inhibitory activity. This activity is regulated by key excitatory (NMDA, AMPA) and inhibitory (GABAA) receptors. The composition of these receptors changes developmentally, affecting the excitatory-inhibitory (E/I) balance and synaptic plasticity. Until now, it has been unclear how abnormal visual experience affects this balance. To examine this question, we measured developmental changes in excitatory and inhibitory receptor subunits in visual cortex following normal visual experience and monocular deprivation. We used Western blot analysis to quantify expression of excitatory (NR1, NR2A, NR2B, GluR2) and inhibitory (GABAAα1, GABAAα3) receptor subunits. Monocular deprivation promoted a complex pattern of changes in receptor subunit expression that varied with age and was most severe in the region of visual cortex representing the central visual field. To characterize the multidimensional pattern of experience-dependent change in these synaptic mechanisms, we applied a neuroinformatics approach using Principal Component Analysis (PCA). We found that monocular deprivation (i) causes a large portion of the normal developmental trajectory to be bypassed, (ii) shifts the E/I balance in favour of more inhibition, and (iii) accelerates the maturation of receptor subunits. Taken together, these results reveal that monocularly deprived animals lack the synaptic machinery needed for functional maturation of cortical circuits and for developmental plasticity. This raises the possibility that interventions intended to treat amblyopia may need to address multiple synaptic mechanisms to produce optimal recovery.